Network analysis of negative emotions in patients with episodic migraine: need for a multidisciplinary perspective - Guerra, Federica; Di Giacomo, Dina; Ranieri, Jessica; Saporito, Gennaro; Sucapane, Patrizia; Totaro, Rocco; Pistoia, Francesca (Frontiers in Neurology, 2024)
Background Episodic migraine (EM) is the second most prevalent neurological disorder worldwide and is responsible for more disability than all other neurological disorders combined. Triggers for the development of migraine include, stress, emotional burden, low blood sugar levels, tobacco, skipped meals, anxious and depressive feelings. Migraine affects both children and adults, occurring three times more frequently in women than in men. Objective The aim of this study was to evaluate the psychological profile of EM patients and the relationship among negative emotions in EM patients, analyzing self-efficacy measures in pain management. Design We performed an observational study in 60 outpatients aged 18–55 years (mean age 33.8; SD ±10.4) with EM. Methods All patients have been enrolled at the Headache Center of the San Salvatore Hospital of L’Aquila. The assessment comprised five standardized psychological self-assessments investigating relevant emotional dimensions and pain self-efficacy, along with two questionnaires assessing migraine-related disability. A network analysis of negative emotions was performed to evaluate which emotional traits and relationships play a crucial role in pain coping and management. Results Our findings indicate that migraine significantly impairs the quality of life of patients in their daily lives. Over half of the patients reported experiencing severe disability, with negative emotions significantly influencing their ability to cope with pain and maintain productivity during migraine attacks. Dysphoric variables (irritability, interpersonal resentment, and surrender) were correlated with difficulties in emotion regulation ability and with the capacity of engaging in goal-directed behaviors despite experiencing pain. The ability to regulate one’s emotions and manage dysphoria were positively correlated with pain self-efficacy, whereas positive mental health was associated with individuals’ confidence in performing activities despite experiencing pain. Conclusion Negative emotions had a negative correlation with positive mental health and were linked to a lower capacity to carry out daily activities despite experiencing migraine pain. This suggests that psychological interventions could improve mental health and potentially surpassing the effects of pharmacological interventions alone in migraine management. An integrated, patient-centered approach may represent an effective paradigm to address and reduce the burden of migraine, leading to a reduction in healthcare costs.